A STUDY OF THE INFLUENCE OF SOCIAL MEDIA COMMUNICATION TECHNOLOGIES ON FAMILY RELATIONSHIPS IN THE KINGDOM OF SAUDI ARABIA - Alanazi, Norah Farhan (Journal of Humanities & Social Sciences, 2018)
This study investigates the effects of using social media communication on family relationships in the Kingdom of Saudi Arabia. A quantitative methodology with a descriptive design was used to determine the relationship between the independent variable (family relationships) and the dependent variable (social media communication). There were 499 participants involved in this research survey, and their ages ranged from 20-50 years up for both males and females. The research shows that there is no significant social media communication effect on relationships between family members, including husband and wife and parent-children, in the Kingdom of Saudi Arabia. The finding shows that participants do not agree that social media influences relationships with married partners and family members. Even though the usage of social media has become a phenomenon in recent days, Saudi Arabian families are still keeping their strong and traditional relationships.